1975
DOI: 10.4159/harvard.9780674365063
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy Versus Behavior Therapy

Abstract: The active, and sometimes It provides a balanced, heated, controversy between objective, and informative look at advocates of these two modes of both sides of one of the most controtherapy has raged despite a versial issues in psychiatry today, shortage of solid information. R. Bruce Sloane, M.D., is But now we have the results chairman of the Department of of a rigorously controlled study Psychiatry, School of Medicine, with actual patients, experienced University of Southern California, therapists, and frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
253
0
11

Year Published

1980
1980
2000
2000

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 540 publications
(277 citation statements)
references
References 0 publications
13
253
0
11
Order By: Relevance
“…The most frequently employed set of techniques in practice were such enhancement methods as increasing therapist-client similarity, use of empathy, verbal reinforcement, structuring, and increasing positive expectancies (Swan, 1979). Sloane, Staples, Cristol, Yorkston, and Whipple (1975), in a carefully controlled clinical study, found that behavior therapists showed significantly higher levels of accurate empathy and congruence than did psychotherapists. Both showed equally high levels of warmth.…”
Section: O 3 ^mentioning
confidence: 99%
“…The most frequently employed set of techniques in practice were such enhancement methods as increasing therapist-client similarity, use of empathy, verbal reinforcement, structuring, and increasing positive expectancies (Swan, 1979). Sloane, Staples, Cristol, Yorkston, and Whipple (1975), in a carefully controlled clinical study, found that behavior therapists showed significantly higher levels of accurate empathy and congruence than did psychotherapists. Both showed equally high levels of warmth.…”
Section: O 3 ^mentioning
confidence: 99%
“…A widely publicized study by Sloane, Staples, Cristol, Yorkston, and Whipple (1975) comparing the relative efficacy of behavioral therapy and psychotherapy, similarly contains the usual share of confounded variables, unmatched mixtures of dysfunctions, and inadequately measured outcomes relying on amorphous clinical ratings rather than on direct assessment of behavioral functioning. As is now predictable for studies of this type, the different forms of treatment appear comparable and better than nothing on some of the global ratings but not on others.…”
Section: The Uniformity Problemmentioning
confidence: 99%
“…A further development has been the use of serial ratings of'target' symptoms. This approach has been effectively employed with neurotic disorders (Gelder et al 1967;Sloane et al 1975). It entails the definition, on a case by case basis, of the specific schizophrenic symptoms that each patient is known to have exhibited prominently during prior exacerbations, and the rating of their severity at regular intervals, and during suspected exacerbations.…”
Section: Discussionmentioning
confidence: 99%